Endemic HBV among hospital in-patients in Bangladesh, including evidence of occult infection. (30th July 2021) - Chowdhury, Fazle Rabbi; McNaughton, Anna L.; Amin, Mohammad Robed; Barai, Lovely; Saha, Mili Rani; Rahman, Tanjila; Das, Bikash Chandra; Hasan, M. Rokibul; Islam, K. M. Shahidul; Faiz, M. A.; Al-Mahtab, Mamun; Mokaya, Jolynne; et al.
Abstract : Bangladesh is one of the top-ten most heavily burdened countries for viral hepatitis, with hepatitis B (HBV) infections responsible for the majority of cases. Recombinant and occult HBV infections (OBI) have been reported previously in the region. We investigated an adult fever cohort ( n =201) recruited in Dhaka, to determine the prevalence of HBV and OBI. A target-enrichment deep sequencing pipeline was applied to samples with HBV DNA >3.0 log10 IU ml −1 . HBV infection was present in 16/201 (8 %), among whom 3/16 (19 %) were defined as OBI (HBsAg-negative but detectable HBV DNA). Whole genome deep sequences (WGS) were obtained for four cases, identifying genotypes A, C and D. One OBI case had sufficient DNA for sequencing, revealing multiple polymorphisms in the surface gene that may contribute to the occult phenotype. We identified mutations associated with nucleos(t)ide analogue resistance in 3/4 samples sequenced, although the clinical significance in this cohort is unknown. The high prevalence of HBV in this setting illustrates the importance of opportunistic clinical screening and DNA testing of transfusion products to minimise OBI transmission. WGS can inform understanding of diverse disease phenotypes, supporting progress towards international targets for HBV elimination.